The interleukin-1 receptor-associated kinases: critical regulators of innate immune signalling - BOWIE, ANDREW; FLANNERY, SINEAD (Elsevier, 2010)
The interleukin-receptor-associated kinase (IRAK) family are involved in regulating Toll-like receptor (TLR) and interleukin-1 (IL-1) signalling pathways. TLRs are pattern recognition receptors of the innate immune response that are responsible for sensing pathogens and initiating immunity, while IL-1 is one of the key cytokines that mediates inflammation. As such, IL-1/TLR signalling pathways and the IRAK family are critical in anti-pathogen responses, inflammation and autoimmunity. The family comprises of four members, IRAK-1, IRAK-2, IRAK-M (IRAK-3) and IRAK-4, and has a role in both positive and negative regulation of signal transduction. While it was once thought that the family displayed some redundancy, each member of the family is emerging as a distinct and vital contributor to IL-1/TLR signalling mechanisms. Knockout mouse studies have explored the relative contribution of each of the IRAKs in IL-1/TLR signalling, while the recent generation of kinase-inactive knock-in IRAK-4 mice have revealed which of IRAK-4 functions require its kinase activity. IRAK-2, previously thought of as a pseudokinase, has recently been proposed to have kinase activity that is essential for TLR signalling. Not surprisingly given their critical role in IL-1/TLR signalling, the IRAK family members have been implicated in certain disease models including human immunodeficiencies. Thus the potential targeting of these essential protein kinases therapeutically is also discussed.
PUBLISHED
Keywords: Immunology; cytokines; Interleukin-1